2015
DOI: 10.2298/tsci1504235d
|View full text |Cite
|
Sign up to set email alerts
|

Flow and deposition characteristics of nanoparticles in a 90° square bend

Abstract: Large eddy simulation and discrete particle model have been used to study the nanoparticles through a 90? square bend flow considering the effects of Brownian motion and turbulence diffusion. The penetration rate and the residence time of particles are evaluated under different flow conditions and various particle sizes. Results show that particles penetration rate increases with an increase in Dean and Schmidt numbers. The particle size and flow Dean number have significantly effects on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…From the previous papers [1][2][3][4][5][6][7][8][9][10][11] it was concluded that the behavior of flow through a curved channel is different from its behavior through a straights channel. The presence of the bend portion along the curved channel creates a centrifugal force which is exerted on fluid flow and as consequence the axial velocity profiles at different cross-section become asymmetric.…”
Section: Introductionmentioning
confidence: 99%
“…From the previous papers [1][2][3][4][5][6][7][8][9][10][11] it was concluded that the behavior of flow through a curved channel is different from its behavior through a straights channel. The presence of the bend portion along the curved channel creates a centrifugal force which is exerted on fluid flow and as consequence the axial velocity profiles at different cross-section become asymmetric.…”
Section: Introductionmentioning
confidence: 99%
“…( ) cross section area wetted perimeter (2) From the Dean number expression, it is evident that the instability of flow through a curved duct depends on large number of fluid parameters and geometrical configurations such as the kind of fluid (Newtonian or non-Newtonian) [3][4][5], the duct cross-sectional form (circular [2], triangular [6], square [7][8], elliptical [9]), the value of curvature radius [10] and finally the external forces exerted on the flow as electromagnetic force [11]. For example the investigation of Dean [2] that is carried out for curved channel of circular cross-section showed that above the critical value of Dean number, new kind of counter-rotating vortices (pair) are observed to appeared on outer wall of duct.…”
Section: Introductionmentioning
confidence: 99%
“…The Dean number shows that the dean vortex size depends on many fluidic parameters as well as geometrical configurations. Examples including: the type fluid (Newtonian or non-Newtonian) [3][4][5], the form of duct cross-section (circular [2], triangular [6], square [7][8], elliptical [9]), the value of curvature radius [10] and the external force acting on the fluid flow as electromagnetic force [11].…”
Section: Introductionmentioning
confidence: 99%